Comparative Evaluation of Conventional and Advanced MRI Sequences in Detecting White Matter Abnormalities - Kumar, Dheeraj; Rastogi, Rajul (Journal of Neonatal Surgery, 2025)
Background: White matter (WM) abnormalities underlie a range of neurological diseases, such as multiple sclerosis, vascular dementia, and traumatic brain injury. Standard MRI sequences (T2-weighted, T2 FLAIR, DWI/ADC) are standardly employed for WM lesion detection but possibly insensitive to microstructural alterations. More sophisticated methods such as Diffusion Tensor Imaging (DTI) and Double Inversion Recovery (DIR) provide enhanced WM characterization but need systematic evaluation against standard approaches. Aim: This research endeavoured to contrast the diagnostic accuracy of routine and high-end MRI sequences for the identification of WM abnormalities, determining lesion conspicuity, and evaluating microstructural integrity. Materials and Methods: A cross-sectional study was conducted on 44 patients (mean age: 41.11 ± 13.51 years; 54.5% female) with suspected WM pathology. Conventional (T2W, T2 FLAIR, DWI/ADC) and advanced (DTI, DIR) sequences were performed on a 1.5T MRI scanner. Quantitative analysis included lesion size, fractional anisotropy (FA), mean diffusivity (MD), and qualitative assessment by radiologists. Statistical analyses (paired t-tests, Wilcoxon signed-rank, Chi-square, Spearman’s correlation) were performed using SPSS (p < 0.05). Results: Lesion distribution analysis demonstrated that the most frequently affected area was subcortical white matter, with involvement seen in 31.8% of the cases on T2-weighted (T2W) imaging and 34.1% on T2 fluid-attenuated inversion recovery (FLAIR) sequences. Among the cerebral lobes, the frontal lobe had the greatest lesion burden at 38.6%, followed by the occipital lobe at 34.1%. Regarding lesion conspicuity, no statistically significant difference existed between double inversion recovery (DIR) sequences and T2 FLAIR sequences (p = 0.560). Diffusion tensor imaging (DTI) values, i.e., fractional anisotropy (FA) with a mean of 0.43 ± 0.097 and mean diffusivity (MD) with a mean of 0.00080 ± 0.0001 mm²/s, were not significantly different in patients with and without white matter tract abnormalities (p > 0.05). Temporal lobe lesions were all but chronic and were found to approach statistical significance (p = 0.059), with the likelihood ratio test demonstrating this relationship (p = 0.015). Conclusion: Standard MRI sequences are still effective for WM lesion detection, and DTI and DIR offer additional microstructural and cortical lesion information. T2 FLAIR should be used for standard screening, with DTI and DIR confined to specialist use. High-field MRI and histopathological correlations should be investigated in further studies.